Association between high sensitivity C-reactive protein and coronary atherosclerosis in a general middle-aged population. (3rd October 2022) - Cederstrom, S; Lundman, P; Alfredsson, J; Hagstrom, E; Ravn-Fischer, A; Soderberg, S; Yndigegn, T; Tornvall, P; Jernberg, T
Abstract: Background: Despite abundant knowledge about the relationship between inflammation and coronary artery disease (CAD), it is still unknown whether high sensitivity C-reactive protein (hsCRP) is associated with coronary atherosclerosis in the general population. Objectives: The project aimed to study the association between systemic inflammation, measured as hsCRP, and coronary artery atherosclerosis in a large population based cohort. Methods: 30, 154 randomly selected men and women aged between 50 and 64 years were included in the SCAPIS (Swedish Cardiopulmonary Bioimage Study). After excluding those not undergoing coronary computed tomography angiography (CCTA), those with proximal segments not technically assessable and those with missing values of hsCRP, 25, 408 individuals were analysed. Coronary artery atherosclerosis was defined as presence of plaque of any degree (1–49% or ≥50% diameter stenosis) or segments not assessable due to calcification in any of the 18 coronary segments. Analysis of severe atherosclerosis included participants with ≥50% diameter stenosis in any of the left main coronary artery (LMCA), the proximal left anterior descending artery (LAD) or three vessel disease including ≥50% diameter stenosis in any of the segments in each of the LAD, right coronary artery (RCA) and circumflex artery (CX). Participants with hsCRP above the lowest detection limit (≥0.7mg/L) were divided into tertiles and compared with hsCRP<0.7 mg/L as a reference. Results: The highest tertile of measurable hsCRP (≥2.3 mg/L) was associated with coronary atherosclerosis in a multivariate analysis adjusted for classical cardiovascular risk factors (Table 1). HsCRP was also related to atherosclerosis with significant coronary artery diameter stenosis ≥50%, ≥4 segments involved, severe atherosclerosis and atherosclerosis with noncalcified plaques. Also, moderately elevated hsCRP (1.2–2.2 mg/L) was significant associated with noncalcified plaques. In a stratified analysis, coronary atherosclerosis was associated with the two highest tertiles of hsCRP (≥1.2 mg/L) in women, but not in men. Conclusion: Elevated hsCRP was associated with the prevalence of coronary atherosclerosis in a population based cohort of middle-aged men and women. The relationships were more pronounced for atherosclerosis with noncalcified plaques and in women compared to men. This suggests that more attention should be given to hsCRP in risk assessment in middle-aged individuals without known disease, especially in women. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): The Swedish Heart Lung FoundationKnut and Alice Wallenberg Foundation